Suitability analysis of prefabricated underground utility tunnels crossing active ground fissures - Qiang Xu; Lei Qiu; Jianbing Peng; Chaoyu Bai; Shuguang Chang; Quanzhong Lu; Wenyang Li; Junyan Zhao; Haoran Chen; Feifan Chen (Alexandria Engineering Journal)
The city of Xi’an, Shaanxi, China, is the transportation hub in western China, which has planned to establish an underground utility tunnel system. However, this city has faced a series of fissure disasters with a wide area of 250 km2, which is hazardous to the safety of the operation and maintenance of tunnels. The results of finite element simulation suggest that prefabricated utility tunnels can better adapt to the activity of the ground fissures. Based on the results, this paper quantifies the maximum ground fissure settlement that the tunnel can bear and compares and analyzes several different working conditions such as crossing angles, and prestressing-pretensioning values. The results show that the main form of damage in the utility tunnel under the activity of surface cracks is the failure of the rubber waterproofing of the joints. To minimize this risk, this paper proposes a method of increasing the prestress to improve the rubber waterproofing performance. This conclusion can effectively increase the operation safety of the utility tunnel.